2010
DOI: 10.1021/om100238w
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Behavior of the Schiff Base Ligand 2,5-Me2C6H3C(H)═N(2,4,6-Me3C6H2) toward Cyclometalation Reactions: C(sp2,phenyl)−H vs C(sp3,methyl)−H Activation

Abstract: Treatment of the Schiff base ligand a with palladium(II) acetate in toluene gave 1a, with metalation of an aromatic phenyl carbon atom. Reaction at room temperature gave the trinuclear complex 4a. Treatment of a with palladium(II) acetate in refluxing acetic acid gave 1a′. The reaction of complexes 1a and 1a′ with sodium chloride or lithium bromide gave the halogen-bridged complexes 2a, 3a, 2a′, and 3a′.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
4
7
0
Order By: Relevance
“…In the case of aliphatic C­(sp 3 )–H bond activation, such precoordination does not occur. ,, In addition, the enhanced flexibility of the aliphatic backbone complicates the selective generation of the well-defined compounds. There are indeed only a few reports in the literature in which the M–C­(sp 3 ) bond formation was promoted over the M–C­(sp 2 ) formation …”
Section: Resultssupporting
confidence: 65%
“…In the case of aliphatic C­(sp 3 )–H bond activation, such precoordination does not occur. ,, In addition, the enhanced flexibility of the aliphatic backbone complicates the selective generation of the well-defined compounds. There are indeed only a few reports in the literature in which the M–C­(sp 3 ) bond formation was promoted over the M–C­(sp 2 ) formation …”
Section: Resultssupporting
confidence: 65%
“…The incorporation of these bioactive Schiff base ligands with Ru‐ p ‐cymene moiety would enhance the synergetic effect, which could be used to develop effective drugs for cancer therapy. The Schiff base ligands, apart from developing as chemotherapeutic elements, may play a vital role in the mechanism underlying catalysis of C‐H activation …”
Section: Introductionmentioning
confidence: 99%
“…For the intramolecular C–H bond activation by palladium(II) and platinum(II), it is generally observed that aromatic over aliphatic C–H bond activation is preferred. Nevertheless, examples have been reported of preferred or selectively directed sp 3 C–H over sp 2 C–H bond activation by palladium(II) and platinum(II). , Factors which can influence the preference in the competing sp 2 vs sp 3 C–H bond activation include metal precursors, ,− solvent, ,, reaction temperature , and the ring size of the metallacycle. ,, Five-membered metallacycles are usually preferred over six-membered ones, although specific features of the preligands can override this trend; this is the case of imines which show a strong preference for the formation of endo complexesthe so-called endo effectover the alternative exo derivatives …”
Section: Introductionmentioning
confidence: 99%